2010
DOI: 10.11120/ital.2010.09010032
|View full text |Cite
|
Sign up to set email alerts
|

A Note on Performance and Satisfaction of Female Students Studying Computer Science

Abstract: In this paper some gender related results are presented. They are taken from a survey conducted at

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 14 publications
(35 reference statements)
0
2
0
Order By: Relevance
“…Other studies have contradicted these findings. In Serbia, one study (Mirjana, Zoran, Anja, & Zoran, 2010) found female students had a high level of confidence in computer science. Confidence is an important component in developing a computer identity which is imperative for women to persist in computer science (Lehman et al, 2016).…”
Section: Self-efficacymentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies have contradicted these findings. In Serbia, one study (Mirjana, Zoran, Anja, & Zoran, 2010) found female students had a high level of confidence in computer science. Confidence is an important component in developing a computer identity which is imperative for women to persist in computer science (Lehman et al, 2016).…”
Section: Self-efficacymentioning
confidence: 99%
“…Other countries, such as Australia (Zagami et al, 2015) and Greece (Wagner, 2016), are also experiencing a shortage of women in the field. However, it is important to note that countries like Armenia and other republics of the former Soviet Union do not report gender inequity in computer science (Gharibyan & Gunsaulus, 2006;Mirjana et al, 2010). In countries like Taiwan, more women successfully complete computer science courses, but these women do not end up working as programmers (Michell, et al, 2017).…”
Section: Cultural Changementioning
confidence: 99%